Orientation loss of microcrystals of DyBa2Cu3Oy in a polymer composite during curing of the medium under an external magnetic field. Issue 34 (12th August 2020) - Kimura, Tsunehisa; Kashiwagi, Hayato; Kimura, Fumiko; Horii, Shigeru; Takeda, Kazuki; Doi, Toshiya
Abstract : The orientation loss of microcrystals during solidifying the matrix in a magnetic field was modeled. In situ X-ray diffraction results obtained for the consolidation process of DyBa2 Cu3 O y microcrystal suspension were explained by the model presented. Abstract : A liquid medium containing microcrystals of DyBa2 Cu3 O y with y ∼ 7 (Dy123) was cured under a magnetic field, and the change in crystal orientation during the curing was monitored by means of in situ X-ray diffraction measurement. The initially achieved crystal orientation deteriorated as curing proceeded. We present a model that explains the experimental results. The model showed that the orientation loss depends on the particle size, degree of shrinkage, initial viscosity of the matrix, and cure rate. We found that there are optimum conditions that minimize the deterioration of the orientation.